Relative influence of musical and linguistic experience on early cortical processing of pitch contours - Chandrasekaran, Bharath (2008)
To assess domain specificity of experience dependent pitch representation we evaluated the mismatch negativity (MMN) and discrimination judgments of English musicians, English nonmusicians, and native Chinese for pitch contours presented in a non-speech context using a passive oddball paradigm. Stimuli consisted of homologues of Mandarin high rising (T2) and high level (T1) tones, and a linear rising ramp (T2L). One condition involved a between-category contrast (T1/T2), the other, a within-category contrast (T2L/T2). Irrespective of condition, musicians and Chinese showed larger MMN responses than nonmusicians; Chinese larger than musicians. Chinese, however, were less accurate than nonnatives in overt discrimination of T2L and T2. Taken together, these findings suggest that experience-dependent effects to pitch contours are domain-general and not driven by linguistic categories. Yet specific differences in long-term experience in pitch processing between domains (music vs. language) may lead to gradations in cortical plasticity to pitch contours.